(untitled) (Journal of Business Management and Accounting, 2023)
Human resources (HR) plays a key role in any business, regardless of its size. Besides recruiting new hires and optimizing existing staff to keep a business running smoothly, HR is also responsible for boosting employee engagement and productivity. Despite the importance of human resource management (HRM) to every organization’s efficiency, micro-businesses struggle with HR challenges such as staff recruitment, training, and retention. Small businesses, especially family-owned ones, often view HRM as an unnecessary investment. This case study examined appropriate HR activities at a micro-enterprise named “Kak Yus Soya.” The purpose of this case study was to identify disparities between Kak Yus Soya’s HR practices and a theoretical HR framework. The next course of action was to evaluate the company’s preparedness to implement HRM and, from there, to design the most suitable HRM framework in light of the organization’s needs and capabilities. The case study objectives were fulfilled by employing a mixed-method approach that combined qualitative and quantitative data collection. The data-collecting process was designed to allow continuity between the objectives of the case study, where each objective was related to bridging the HR gaps in the organization, which subsequently aided in developing a practical HR framework for Kak Yus Soya. At the end of the study, a structured HRM model for micro-enterprises was created in accordance with the theoretical framework that served as the foundation of this case study. The established HR framework integrated five HR activities: i) assessing employer readiness, ii) HR planning, iii) selection and recruitment, iv) training, and v) performance appraisal. These activities are the fundamental components that a good HRM system must contain.